Exposing Causative Factors on Software Discontinuity using an Elaborative Qualitative Method - Gandhi, Arfive; Kusumo, Dana Sulistiyo; Sardi, Indra Lukmana (Journal of Information Systems Engineering and Business Intelligence, 2025)
Background: Software discontinuity due to the inability to accommodate the needs of users is a the significant challenge facing the software development life cycle. This implied that the development team must be capable of producing software with extended lifespan, including the ability to detect outages early, to maintain continuity. Organizations need to determine the contributing and inhibiting factors responsible for discontinuity usage.  Objective: This research aimed to explore the factors that contribute and inhibit the discontinuation of software use in organizations as well as the prevention strategies.  Methods: The summative content analysis technique was used to capture, codify, and classify statements from respondents to discover usage pattern. Data were collected through interview and questionnaire techniques with 10 respondents from various Indonesian companies. The respondents had various sectoral backgrounds in software usage for more than a year. The data collected were compared, contrasted, and synthesized to deliver a holistic pattern among respondents.  Results: The result showed that 10 key factors contributed to software discontinuity, namely Loss of Perceived Usefulness (LUS), Loss of Perceived Ease of Use (LEU), Decreased Effort Expectancy (DEX), Decreased Performance Expectancy (DPX), Social Influence (SOI), Lack of Facilitating Conditions (LFC), Decreased Price Value (DPV), Lack of Habit (LHB), Hedonic Motivation (HDM), and Loss of Perceived Behavioral Control (LBC). The factors were further categorized into three big issues, including Software Usability (LUS, LEU, DEX, and DPX), External Triggers (DPV, SOI, and LBC), and Risk Management after Discontinuity (LFC, LHB, and SOI). Furthermore, the results indicated that nine factors contributed to software discontinuity except HDM with LEU and LUS having weak significance since most respondents stated partial agreement and disagreements.  Conclusion: This research employed a rigorous qualitative method to validate the factors in the proposed software discontinuity model with 10 causative factors. The acquired knowledge is expected to aid organizations or related development units to build software that accommodates user needs, including meeting long-term business targets.  Keywords: Software, Software Discontinuity, Influencing Factors, Qualitative Method